In-Situ GISAXS Study of Supramolecular Nanofibers having Ultrafast Humidity Sensitivity - Arpan Bhattacharyya (Nature Portfolio, 2017)
Abstract Self assembled nanofibers derived from donor-acceptor (D-A) pair of dodecyl methyl viologen (DMV) and potassium salt of coronene tetracarboxylate (CS) is an excellent material for the development of organic electronic devices particularly for ultrafast response to relative humidity (RH). Here we have presented the results of in-situ grazing incidence small angle x-ray scattering (GISAXS) measurements to understand aridity dependent self reorganization of the nanofibers. The instantaneous changes in the organization of the nanofibers was monitored with different equilibrium RH conditions. Additionally formation of nanofibers during drying was studied by GISAXS technique – the results show two distinct stages of structural arrangements, first the formation of a lamellar mesophase and then, the evolution of a distorted hexagonal lattice. The RH dependent GISAXS results revealed a high degree of swelling in the lattice of the micelles and reduction in the distortion of the hexagonal structure with increase in RH. In high RH condition, the nanofibers show elliptical distortion but could not break into lamellar phase as observed during formation through drying. This observed structural deformation gives insight into nanoscopic structural changes of the micelles with change in RH around it and in turn explains ultrafast sensitivity in its conductivity for RH variation.